Potensi Aktivitas Ekstrak Etanol Rimpang Kunyit (Curcuma longa) sebagai Antibakteri Escherichia coli - Suci Wulandari; Aminah Syarifuddin; Cucu Arum Dwi Cahya; Pebriani Nainggolan (Jurnal Indah Sains dan Klinis, 2023)
Background: Turmeric (Curcuma longa) is well known as one of the many medicinal plants in the form of rhizomes, both on a home and industrial scale. The chemical components contained in the rhizomes include fat, ascorbate, protein, starch, tannin, curcumin, flavonoids and essential oils. Turmeric is commonly used by people to reduce the frequency of diarrhea. Apart from having chelating properties, it is also anti-inflammatory and even antibacterial. Objective: The study was directed to investigate the potential of ethanol extract of turmeric rhizomes (EERK) on Escherichia coli. Method: Dry rhizome powder was macerated using 96% ethanol, then rotary evaporated to obtain dry turmeric rhizome extract (EKRK), and divided into concentrations of 30%, 40% 50%, positive or negative control. Results: The study shows that there is an influence of EKRK concentration on the antibacterial potential of Escherchia coli. One-way ANOVA described that there was a significant difference (p < 0.010) in the use of various EKRK concentrations as inhibitors of bacterial growth and development. Antibacterial activity at 30, 40, and 50 % was 14.3, 17.5, and 19.7 mm, respectively. Conclusion: EERK has strong potential as an antibacterial for Escherichia coli.